2005
DOI: 10.1080/00365520500217043
|View full text |Cite
|
Sign up to set email alerts
|

Is the questionnaire for the assessment of gastroesophageal reflux useful for diabetic patients?

Abstract: The questionnaire was shown not to be useful for diagnosing GER as a complication in diabetic patients. We, therefore, should not diagnose GER as a complication in diabetes mellitus on the basis of the questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…These findings were also supported by Kinekawa et al [21], who hardly found any reflux symptoms in 53 patients investigated by a structured questionnaire. Autonomic NP with damage of efferent and afferent nerve fibers has been made responsible for this phenomenon and it was concluded that GERD questionnaires were not useful for diabetic patients [21]. However, one may criticize that both authors [11,21] used questionnaires which have not been validated and lack adequate reliability and responsiveness [22][23][24].…”
Section: Gerd Related Symptomssupporting
confidence: 75%
See 1 more Smart Citation
“…These findings were also supported by Kinekawa et al [21], who hardly found any reflux symptoms in 53 patients investigated by a structured questionnaire. Autonomic NP with damage of efferent and afferent nerve fibers has been made responsible for this phenomenon and it was concluded that GERD questionnaires were not useful for diabetic patients [21]. However, one may criticize that both authors [11,21] used questionnaires which have not been validated and lack adequate reliability and responsiveness [22][23][24].…”
Section: Gerd Related Symptomssupporting
confidence: 75%
“…Interestingly, patients with end-stage diseases suffering from DM type II for more than 16 years show a decrease of reflux symptoms [11]. These findings were also supported by Kinekawa et al [21], who hardly found any reflux symptoms in 53 patients investigated by a structured questionnaire. Autonomic NP with damage of efferent and afferent nerve fibers has been made responsible for this phenomenon and it was concluded that GERD questionnaires were not useful for diabetic patients [21].…”
Section: Gerd Related Symptomsmentioning
confidence: 65%
“…There is another important issue concerning GERD in diabetic patients. Kinekawa et al [124] examined 53 diabetic patients by QUEST immediately before 24-h pH monitoring. They found that diabetic patients had fewer symptoms and extremely low scores, and there was no difference in scores between patients with and without GER.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…37,38 Consequently, an exact evaluation of esophageal dysfunction on the basis of symptoms may be diffi cult in patients with diabetes. 4,39 Typical refl ux symptoms may be vague in diabetic patients. Another questionnaire, for example, the GSRS 40 or FSSG, 41 which can evaluate abdominal discomfort or dysmotility symptoms, may be more suitable in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%